Current Situation of Breast Cancer in Pakistan and the Dire Need of Early Diagnosis - Khan, Najeeb Ullah; Khan, Bibi Maryam; Azam, Imad; Hayat, Atif (Current Trends in OMICS, 2024)
Globocan statistics underscore Pakistan’s noticeable position in terms of the breast cancer burden, highlighting a concerning and escalating trajectory in its daily progression. Breast cancer stands as the most predominant and fatal malignancy in Pakistan, reporting 25,928 cases in the year 2020, accounting for 14% of all cancer diagnosis. The country is reported to have the maximum incidence and mortality rates in Asia, a dire result of the lack of national cancer registry. Late diagnosis, often determined by sociocultural factors, considerably contributes to the high mortality rate. Several risk factors, such as reproductive factors, age, dietary habits, further complicate the situation. Moreover, economic obstacles deter many from receiving the required treatment. The current review features the dire need for inclusive policies and improved affordability to battle breast cancer’s escalating influence in Pakistan.